Book Review: Social Stock Exchanges: Catalyst for Impact Investing? - PARVEEN KAUR HARNAM SINGH (Asian Journal of Accounting Perspectives, 2024)
Part of the Springer Sustainable Finance series, this book aims to fill the gap in research on impact exchanges (IE) or social stock exchanges (SSE), which this reviewer concurs is a “young research field.” It also targets “under-researched” institutional investors and the extent to which they can be matched with the alternative asset classes in social entrepreneurship. Employing interviews with members of the European Union High- Level Group, the author, among others, reviews the literature on current taxonomies, the current state of SSEs, considers what it currently does well, what can be improved, and how it impacts capital redirection in the financial market. With the Malaysian prime minister recently announcing the launch of “Malaysia’s first social exchange” fronted by the Securities Commission (SC), and its incoming framework (SC, 2024; Tay, 2024), this book has layered appeal, from impact funders to academicians. In this region, the book acts as a precursor to the concept of SSEs for policymakers, stakeholders, regulatory agencies, impact funders, and even social enterprises, as well as nongovernmental organisations exploring more structured alternative financing. As it focuses on IEs and SSEs within the larger context of impact investing, it should also be on the bookshelves of academicians or researchers who are interested in the future direction of the increasingly converging intersection of doing well and doing good, i.e., the comingling of finance and social or environmental goals. A resurgence in adopting SSEs within Asia further makes it all the more relevant to regional policymakers, industry players and academicians alike.